2015
DOI: 10.1039/c5cp03343h
|View full text |Cite
|
Sign up to set email alerts
|

Isotope-edited FTIR reveals distinct aggregation and structural behaviors of unmodified and pyroglutamylated amyloid β peptides

Abstract: Amyloid β peptide (Aβ) is causatively associated with Alzheimer’s disease (AD), and N-terminally truncated and pyroglutamylated Aβ peptides (AβpE) exert hypertoxic effect by an unknown mechanism. Recent evidence has identified the prefibrillar oligomers of Aβ, not the fibrils, as the prevalent cytotoxic species. Structural characterization of Aβ and AβpE oligomers is therefore important for better understanding of their toxic effect. Here we have used isotope-edited Fourier transform infrared (FTIR) spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 91 publications
(227 reference statements)
0
18
0
Order By: Relevance
“…It has been suggested that the lateral or partially stacked non‐H‐bonding interactions are between the N‐terminal strand of one peptide and the C‐terminal strand of the other in a parallel or antiparallel manner. Moreover, the presence of a residual α‐helical segment at the N terminus of the peptide is another characteristic of this oligomer structure . Further evidence for the contribution of α‐helices to oligomer secondary structure was provided by Kirkidatze et al .…”
Section: Experimental Studiesmentioning
confidence: 84%
See 3 more Smart Citations
“…It has been suggested that the lateral or partially stacked non‐H‐bonding interactions are between the N‐terminal strand of one peptide and the C‐terminal strand of the other in a parallel or antiparallel manner. Moreover, the presence of a residual α‐helical segment at the N terminus of the peptide is another characteristic of this oligomer structure . Further evidence for the contribution of α‐helices to oligomer secondary structure was provided by Kirkidatze et al .…”
Section: Experimental Studiesmentioning
confidence: 84%
“…Moreover,t he presence of ar esidual a-helicals egment at the Nterminus of the peptidei sa nother characteristic of this oligomer structure. [118] Further evidencef or the contributiono fa-helices to oligomer secondary structure was providedb yK irkidatze et al [119] They analyzedd ifferent Ab alloforms by CD and found between 20 and 30 % a-helicity for an intermediate structure based on a minimum of 23 Ab monomers.…”
Section: Low-resolution Structural Informationf or Larger Oligomeric mentioning
confidence: 98%
See 2 more Smart Citations
“…The N-terminal region might support the aggregation-prone sequence stabilizing b-sheet formation as described by Abedini and Raleigh (50,51). Similarly, it was shown, using Fourier transform infrared (FTIR) spectroscopy, that Ab forms a transient a-helical structure at the N-terminal region and that the helix stability is modulated by the ionic strength and the N-terminal modification (62).…”
Section: The Very N-terminus Of Ab Affects Its Fibrillization Kineticsmentioning
confidence: 99%